Józef Wittlin’s translation of "The Odyssey" as a declaration of humanism - Józwikowska, Wanda (Traduttologia e Traduzioni, vol. III: Interdisciplinarietà della traduzione, 2021)
This chapter looks at Józef Wittlin’s Polish translation of Homer’s Odyssey as a literary channel to convey the translator’s own very humanist outlook. It focuses, above all, on the translation’s peculiar archaising style, explaining how Wittlin’s philosophical beliefs can be expounded by focusing on the style of the translation rather than on the innate qualities of the Greek epic. The translation’s style then becomes an interdisciplinary focal point in which stylistics and the translator’s personal philosophy converge.